Estudo teórico das propriedades espectroscópicas e estruturais do LiF, EuF3, AF2 (A = Ca, Sr e Ba) dopados com Eu3+ - Mesquita, Bruno Ribeiro de (2021)
A systematic theoretical study of the local symmetry of the Eu3+ in (LiF, EuF3 and the family AF2 (A = Ca, Sr and Ba)) fluorides crystals using crystal field theory applied to lanthanides along with the atomistic computational modelling is presented. The Simple Overlap Model with the Method Equivalent Nearest Neighbours was used in the TCC and in the Auzel-Malta equation to calculate the energy sublevels of the 7F1, 7F2, 5D1 multiplets and the 7F1 split, using a set of phenomenological charge factors. Employing a set of Buckingham short-range interatomic potential parameters and the shell-model, the lattice parameters and the unit cell volume of these crystals were reproduced satisfactorily in good agreement with the experimental data. Because of this, energy calculations of intrinsic, extrinsic bound and unbound defects were obtained using the GULP computational code. The LiF was studied in three situations. In the first case of doping with low concentrations of Eu3+, this trivalent lanthanide occupies a local symmetry without an inversion center because the 0 - 2 transition is more intense than the 0 - 1 transition, in which we indicated the formation of a a-EuF3 polymorphic phase. Thus, with a combination of non-null crystal field parameters, in this case the slightly distorted c2v symmetry is most likely. In the second case of doping with high concentrations of Eu3+ and with 0 - 2 less intense than 0 - 1, and due to the asymmetry of the emission spectrum a graphic deconvolution was performed and two peaks in these transitions were obtained. In this case, the Eu3+ occupies a symmetry with a distorted inversion center, in which we indicated a combination of D4, DAD and D2d symmetries. In the third case and through the atomistic computational simulation with the lowest solution energy by defect, the LiF Anti-Schottky is more favourable intrinsically and the Eu3+ replaces the Li+ site compensated by lithium vacancies extrinsically. By the computationally obtained local structure, the lanthanide occupies a slightly distorted D4 symmetry. The EuF3 was analyzed with two and three lines observed at the 0 - 1 transition. A combination of D3d with D3 and C2 with C2 symmetries are likely for two and three lines, respectively. In the AF2 crystals (A = Ca, Sr and Ba) and considering the bound extrinsic defects, the Eu3+ replaces the site of the A2+ compensated by cationic vacancies and occupies a distorted s6 local symmetry. In all spectroscopic analyses, the B2 0 signal was investigated. A new equation to calculate the charge of the Eu3+ was proposed considering the effects of covalence on the chemical bonding, Brik-Avram overlap integrals, octet rule and chemical valence of the nearest neighbour. The magnitude of this charge was compared with that obtained through the equation presented by the Batista-Longo Improved Model. This indicated that in the Eu3+ - PV interactions (PV = F-, O 2-), the charge is closer to the PV and around the interatomic middle distance. All theoretical calculations performed in this work are in good agreement with the experimental data.